An ultrasensitive human cardiac troponin T graphene screen-printed electrode based on electropolymerized-molecularly imprinted conducting polymer - Silva, Bárbara V.M.; Rodríguez, Blanca A.G.; Sales, Goreti F.; Sotomayor, Maria Del Pilar T. [UNESP]; Dutra, Rosa F. (Elsevier, 2016)
A nano-molecularly imprinted polymer (N-MIP) assembled on a screen-printed electrode for the cardiac troponin T (cTnT) was developed. The biomimetic surface was obtained by a co-polymer matrix assembled on the reduced graphene oxide (RGO) electrode surface. The cTnT active sites were engineered using pyrrole and carboxylated pyrrole that was one-step electropolymerized jointly with cTnT by cyclic voltammetry. The stepwise preparation of the biomimetic surface was characterized by cyclic and differential pulse voltammetries using the ferrocyanide/ferricyanide as redox probe. Structural and morphological characterization was also performed. The optimal relation of pyrrole and pyrrole-3-acid carboxylic to perform the cTnT biomimetic nanosurface was obtained at 1:5 ratio. The analytical performance of cTnT N-MIP performed by differential pulse voltammetry showed a linear range from 0.01 to 0.1ngmL-1 (r=0.995, p«0.01), with a very low limit of detection (0.006ngmL-1). The synergic effect of conductive polymer and graphene forming 3D structures of reactive sites resulted in a N-MIP with excellent affinity to cTnT binding (KD=7.3 10-13molL-1). The N-MIP proposed is based on a simple method of antibody obtaining with a large potential for point-of-care testing applications.
Keywords: Acid carboxylic-3-pyrrole; Cardiac troponin T; Graphene; Molecularly imprinted polymer; Point-of-care testing; Pyrrole